2020
DOI: 10.3390/en13226056
|View full text |Cite
|
Sign up to set email alerts
|

The Enhancement of Energy Efficiency in a Wastewater Treatment Plant through Sustainable Biogas Use: Case Study from Poland

Abstract: The improvement of energy efficiency ensuring high nutrients removal is a great concern for many wastewater treatment plants (WWTPs). The energy balance of a WWTP can be improved through the application of highly efficient digestion or its intensification, e.g., through the introduction of the co-substrates with relatively high energy potential to the sewage sludge (SS). In the present study, the overview of the energetic aspect of the Polish WWTPs was presented. The evaluation of energy consumption at individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…Masłoń et al [69] reported the performance of co-digestion at the WWTP located in Iława (Poland) for a two-year period using as co-substrate poultry fat wastes. These authors observed an increase in biogas production of 82% with an enhancement of 29% in volatile solid removal.…”
Section: Co-digestion Proposed As the Best Way To Take Advantage Of Process Synergiesmentioning
confidence: 99%
“…Masłoń et al [69] reported the performance of co-digestion at the WWTP located in Iława (Poland) for a two-year period using as co-substrate poultry fat wastes. These authors observed an increase in biogas production of 82% with an enhancement of 29% in volatile solid removal.…”
Section: Co-digestion Proposed As the Best Way To Take Advantage Of Process Synergiesmentioning
confidence: 99%
“…The anaerobic digestion process is usually operated in the mesophilic temperature range (35-40 • C) while the action of methanogens bacteria well performs in the pH range 6.8-7.2 [28]. Biogas production per unit mass of volatile solid substance can vary in a wide range of values: for a sludge with 75% of volatile solid and a digestion process time of 21-25 days a specific biogas production of 0.6-0.8 (Nm 3 /kg) of volatile solid can be obtained [8]. Performance measures indexes measuring the efficiency in sludge-to-biogas conversion highly depends on type of sludge.…”
Section: Performance Measures Of Energy Recoverymentioning
confidence: 99%
“…The SS production rate generated from WWT is growing day by day as the water demand, and, thus, the amount of wastewater produced, is on increase [8]. The rapid increase depends on two main factors.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the leading challenge for municipal wastewater treatment plants (WWTPs) staff is to ensure both a high-quality effluent wastewater and reduction of operating costs [Shahzad et al, 2015;Drewnowski et al, 2019;Masłoń et al, 2020]. In particular, large facilities must meet stringent requirements with regard to nitrogen and phosphorus for wastewater discharge to the environment [Mucha and Mikosz, 2021; Jaromin-Gleń et al, 2013; Barbusiński et al, 2020].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, large facilities must meet stringent requirements with regard to nitrogen and phosphorus for wastewater discharge to the environment [Mucha and Mikosz, 2021; Jaromin-Gleń et al, 2013; Barbusiński et al, 2020]. Therefore, advanced treatment technologies should be applied [Roots et al 2020;Shourjehet al, 2020;Czarnota et al, 2020]. It is noteworthy that WWTPs aremodern facilities with high energy consumption, while the treatment process itself is multi-stage and complicated [Zubrowska-Sudol et al, 2018; Kudlek and Dudziak, 2018; Szeląg and Barbusinski 2020], so the additional method of monitoring and control are developed [Guz et al, 2015;Łagód et al, 2019;Byliński et al, 2019].…”
Section: Introductionmentioning
confidence: 99%